2017
DOI: 10.4322/2357-9730.69868
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of N-acetyl-L-cysteine on glutathione and sulfhydryl levels in X-linked adrenoleukodystrophy patients

Abstract: Introduction: Recent evidence shows that oxidative stress seems to be related with the pathophysiology of X-linked adrenoleukodystrophy (X-ALD), a neurodegenerative disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…In an animal model of X-ALD, oxidative damage, metabolic failure and axonal degeneration were reversed following treatment with the antioxidants, n -acetyl cysteine (NAC), α-lipoic acid, and α-tocopherol, providing proof of concept on the pivotal contribution of oxidative damage to disease pathogenesis in addition to illustrating the efficacy of antioxidant interventions [ 128 , 129 , 130 ]. A subsequent human study in X-ALD documented the ability of NAC treatment to replenish plasma GSH levels and ameliorate oxidative damage to proteins under in vitro conditions [ 131 ]. Evidence of decreased plasma CoQ 10 status was reported in patients with a defect in peroxisome β-oxidation enzyme, d -bifunctional protein, which was associated with markers of increased oxidative stress [ 132 ].…”
Section: Peroxisomal Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…In an animal model of X-ALD, oxidative damage, metabolic failure and axonal degeneration were reversed following treatment with the antioxidants, n -acetyl cysteine (NAC), α-lipoic acid, and α-tocopherol, providing proof of concept on the pivotal contribution of oxidative damage to disease pathogenesis in addition to illustrating the efficacy of antioxidant interventions [ 128 , 129 , 130 ]. A subsequent human study in X-ALD documented the ability of NAC treatment to replenish plasma GSH levels and ameliorate oxidative damage to proteins under in vitro conditions [ 131 ]. Evidence of decreased plasma CoQ 10 status was reported in patients with a defect in peroxisome β-oxidation enzyme, d -bifunctional protein, which was associated with markers of increased oxidative stress [ 132 ].…”
Section: Peroxisomal Disordersmentioning
confidence: 99%
“…Evidence of decreased plasma CoQ 10 status was reported in patients with a defect in peroxisome β-oxidation enzyme, d -bifunctional protein, which was associated with markers of increased oxidative stress [ 132 ]. It has been suggested that, based on the integral involvement of oxidative stress in the pathogenesis of peroxisomal disorders, the administration of antioxidants should be considered as a potential adjunct therapy for patients with these diseases [ 109 , 131 , 132 ].…”
Section: Peroxisomal Disordersmentioning
confidence: 99%